Empowering Members of The Ikhwatunnisa Women Farmers Group in Padang Through Training and Mentoring in Nata De Coco Production - Advinda, Linda; Irdawati, Irdawati; Handayani, Dezi; Violita, Violita; Chatri, Moralita; Larashinda, Mentari; Syahrastani, Syahrastani (Fakultas MIPA Universitas Negeri Padang, 2025)
– Coconuts, a major commodity in West Sumatra, often produce wasted coconut water, which causes pollution. To address this issue, training was conducted for member of the Ikhwatunnisa Women Farmers Group on how to make nata de coco from this waste. Nata de coco, a functional food, is produced by fermenting coconut water using Acetobacter xylinum bacteria. The training aimed to empower Ikhwatunnisa Women Farmers Group members with skills to start businesses, create jobs, and increase family income. The training included lectures, demonstrations, and hands-on practice, covering everything from preparation to packaging. Evaluations showed high participant enthusiasm; 85% gained new insights and planned to produce nata de coco independently. This activity is expected to encourage new businesses and transform coconut water waste into a valuable economic product.